MENATA KOMUNIKASI PADA MEDIA SOSIAL ONLINE UNTUK MENGHINDARI JERAT HUKUM - Mahayoni Mahayoni (Bricolage : Jurnal Magister Ilmu Komunikasi, 2015)
AbstrakCurrently the development of on-line world of social media in Indonesia is very rapid. Now even online social media becomes an integral part of society. In addition to the ease of getting the network, the price is more affordable for most people. Unfortunately, the availability of facilities and infrastructure is not accompanied by the readiness of regulation capable of managing communication through social media. Without a rule that organizes and directs users online media resulted in the omission of the online media communities. This situation is exacerbated when directly ahead of the 2014 presidential election through the smear campaign and criticizes each other, mutual blasphemous, to the speech of hatred. Unfortunately, despite the elections have passed, but the use of "hateful speech" did not pass it even more and be so.Law No. 11 of 2008 on Electronic transaction, Government Regulation No.82 of 2012 on the Implementation of the System and Electronic Transactions, had long existed and has been treated even used in criminal cases involving the use of online media. But the proliferation of hate speech and even showed to an incumbent president makes everyone frustrated. Legal action taken is still too little and tends to be selective. Finally the Chief of Police issued a circular No. 6/X/15 the direction for members of the Police prioritize education efforts, mediation, and reconcile disputing parties to prevent collective hatred, exclusion, discrimination and violence. Key word: communication, on-line media, hatred speech